East encounters West - Göçek, Fatma Müge. (New York ; Oxford)
xiii, 192 sayfa
Keywords: “In 1720 an Ottoman ambassador arrived in France to observe Western civilization and report on what he saw and how it could be applied in the Ottoman Empire. Based on his accounts, this book studies the impact of the West on the Empire, and of this Ottoman embassy on the two societies” --